Retrofitting model for existing hospital building to improve energy efficiency towards sustainability / Aisah Rustan ... [et al.] - Rustan, Aisah; Mui, K. W. Horace; Akasah, Zainal Abidin; Zaini, Nik Mohd (2019)
The construction industry is crucial to the Malaysian economy and its growth. Retrofitting such of existing buildings presents can gives the largest potential for the incorporation of renewable energy technologies and energy efficiency measures into buildings. The main purpose of this study is to identify the problem of energy efficiency towards green building sustainability and to analyse the problem that is causing the inefficiency and to develop the retrofitting models to improve the energy efficient for selected existing hospital buildings. In order to carry out this research, a comprehensive literature review was done to gather the information and to help in designing the research questionnaire that will be conducted at Sultanah Nora Ismail Hospital building in identifying the potential improvement. The essential elements in GBI from all aspects under energy efficiency need to be emphasized in order to recognise sustainable buildings.